THE PROFIT SHARING IMPLEMENTATION FOR FINANCING IN INDONESIAN ISLAMIC BANKING - Aidha Trisanty (Airlangga International Journal of Islamic Economics and Finance, 2018)
One of the characteristics of Islamic banking is using the concept of profit sharing. This characteristic distinguishes the operation of Islamic banking with conventional banking. In applying the concept of profit sharing, most of the activities of Islamic banking especially in the distribution of funds or financing are dominated by the profit sharing agreement. However, financing in the Islamic banking today mostly is dominated by features that use nonprofit-sharing agreement such as murabahah. This paper examines why financing non-profit-sharing still dominates the realization of financing of Islamic banking in Indonesia, and what solutions can do to increase the financing based on profit sharing concept. The paper is consistent with the objectives stated in the blueprint for the development of Islamic banking in Indonesia, which states that the vision will achieve ten years. They are to establish Islamic banking system that is competitive, efficient, which meets the prudential principle, and to support the real sector through profit sharing financing and real transactions in the context of fairness, mutual help, and for betterment to achieve the mutual benefits for the society.